2020
DOI: 10.1088/1742-6596/1529/2/022065
|View full text |Cite
|
Sign up to set email alerts
|

Information System Based Excellent Higher Education Model

Abstract: The problem of this study was to find the tool to measure Higher Education. There is no standard of measurement tools for excellent Higher Education. The status of an excellent Higher Education has not been an effective promotion for Higher Educations. Besides, it has not the indicators whether the excellent Higher Education or poor Higher Education. It is reflected by the cluster excellent Higher Education, fair Higher Education and poor Higher Education based on information systems. The purpose of this resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Therefore, scholars from around the world are exploring issues of education and improving its quality, namely: − digital education [4], − a model of a different higher education [5], − digital security [6], − distance learning system [7], − portfolio of vocational education services [8], etc. Having studied the educational direction, the researchers have concluded that there is no formed, recommended structure for the work of educational and methodological support of the educational organization (listeners, teaching employees).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, scholars from around the world are exploring issues of education and improving its quality, namely: − digital education [4], − a model of a different higher education [5], − digital security [6], − distance learning system [7], − portfolio of vocational education services [8], etc. Having studied the educational direction, the researchers have concluded that there is no formed, recommended structure for the work of educational and methodological support of the educational organization (listeners, teaching employees).…”
Section: Methodsmentioning
confidence: 99%